Preliminary study on developing 1,5-Diphenylcarbozone as a chemosensor againts Hg2+ ions recognition in aqueous media - Abdullah, Erna Normaya; Ahmad Hamdan, Mohamad Faiqwan; Ahmad, Mohammad Norazmi; Yunus, Kamaruzzaman; Ku Bulat, Ku Halim (2019)
Mercury is a toxic metal that exist and can be found everywhere in the surrounding as it is used in many products of our daily life and mercury contamination usually cannot be observed by human five senses. Continuous exposure to mercury can cause severe implication to neurologic, gastrointestinal and renal organ systems. This study was conducted to develop a portable and easy to use chemosensor using Diphenylcarbazone (DPCO) for detecting Hg2+ ions in an aqueous system. The sensitivity of DPCO to act as a chemosensor was optimized based on solvent/co-solvent ratio and pH. The result showed that DPCO has a highly sensitivity against Hg2+ in DMSO/citrate buffer (8/2, v/v, pH=4.0). The LOD of DPCO against Hg2+ ions calculated was 13 ppm. The stoichiometric ratio of DPCO-Hg2+ was 1:1, as determined from the Job’s plots analysis. The chemical properties such as sigma profile, MEP, Fukui function and HOMO-LUMO energy of DPCO as a chemosensor were studied using COSMO-RS and DFT methods respectively. The result from the sigma profile calculation showed that DPCO formed stronger hydrogen bonds with the DMSO solvent. From DFT calculation, the HOMO-LUMO energy gap of DPCO and DPCO-Hg2+ were -4.2759 eV and -2.1769 eV, respectively. Test strips of DPCO chemosensor was developed and it showed color change that proved the ability of the DPCO chemosensor to detect Hg2+ in an aqueous medium.